(untitled) (Journal of Finance, Business and Management Studies, 2022)
In today’s situation, the whole world is fighting against the covid 19. In this situation, people are advice to follow certain curfews given by government. This lockdown and curfews created major loss in the business. Nowadays, the industry prefers the Automated Machine AM or robots for their production rather than the employees. So that it can reduce the number of workers in the industry and socialgatherings will be avoided and It will save the salary of employees. And while going with AM it will save time by producing huge number of products and it will also produce with the nil errors. In this covid situation, the logistics and Supply Chain Management SCM has been affected very much. Artificial intelligence AI is the developing field which helps the country to develop their nation’s production. AM are helpful for packing and separating products according to their categories. Investment on AI will be high and it has high ability to sustain for long period. This paper is all about to analyze the Logistics Analytics LA, in that how an AI and AM is helpful for that production. And the impacts caused to the society.